Pengaruh Pendapatan dan Persepsi Orang Tua Mengenai Pembelajaran Online Di Masa Pandemi Covid-19 Terhadap Minat Masuk Perguruan Tinggi di Kecamatan Ende Tengah - Jemimi, Maria Vilani Suriati; Penu, Yustina Paulina; Luciany, Yohanes Paulus (JURNAL EQUILIBRIUM, 2023)
This study aims to determine the effect of income and parental perceptions of online learning during the COVID-19 pandemic on interest in entering higher education in the district of Central Ende. The type of research used is quantitative and qualitative research with observation data collection techniques and questionnaires. The data analysis technique used classical assumption test and multiple regression analysis. The results showed that there was no significant influence between parental income on interest in entering higher education in Central Ende sub-district and there was a positive and significant influence between parents' perceptions of online learning during the COVID-19 pandemic on interest in entering higher education in Central Ende sub-district.